2010
DOI: 10.2169/internalmedicine.49.2175
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Longitudinal Myelitis Associated with Behcet's Disease

Abstract: In neuro-Behcet's disease (NBD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
0
13
0
1
Order By: Relevance
“…In patients with NBD, the spinal cord can be affected, and when the lesion involves mostly the cervical cord, dorsal areas may be affected . On the other hand, much rarer examples of longitudinally extensive lesions have been reported, where the lesions extend in a sagittal or transverse direction (the central gray matter and posterior and lateral funiculi of C1‐Th3, the central gray matter of the entire spinal cord and the transverse plane of the entire Th). The Th lesion of the present NBD patient was different from those previously described.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with NBD, the spinal cord can be affected, and when the lesion involves mostly the cervical cord, dorsal areas may be affected . On the other hand, much rarer examples of longitudinally extensive lesions have been reported, where the lesions extend in a sagittal or transverse direction (the central gray matter and posterior and lateral funiculi of C1‐Th3, the central gray matter of the entire spinal cord and the transverse plane of the entire Th). The Th lesion of the present NBD patient was different from those previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Cord swelling and T2-hyperintense, nonenhancing lesions are present in the acute or subacute phase. 106,107,[109][110][111][112][113][114] An unusual report of TM (extending from T9 to the conus) following CT-guided L2 nerve root injection, may be a florid demonstration of the pathergic reaction in the spinal cord. 115 Brain MRI may reveal T1-hypo/isointense and T2-hyperintense lesions that may or may not show gadolinium enhancement acutely.…”
Section: Behcet Diseasementioning
confidence: 99%
“…Of these 7 patients the myelitis was partial in 3, transverse in 2, and presented as a Brown-Séqard syndrome in 2. In addition to this series a number of case reports describe myelopathic involvement in Behçet's disease (Morrissey et al, 1993a;Yoshioka et al, 1996;Mascalchi et al, 1998;Kocer et al, 1999;Green and Mitchell, 2000;Harmouche et al, 2000;Lee et al, 2001;Lannuzel et al, 2002;Moskau et al, 2003;Calguneri et al, 2005;Deshpande et al, 2005;Mullins et al, 2009;Fukae et al, 2010;Metreau-Vastel et al, 2010). Behçet's associated myelitis is typically longitudinally extensive and extension of upper cervical cord lesions into brainstem structures can occur.…”
Section: Behçet's Diseasementioning
confidence: 90%
“…Behçet's associated myelitis is typically longitudinally extensive and extension of upper cervical cord lesions into brainstem structures can occur. Single vertebral segment involvement is reported (Kidd et al, 1999;Calguneri et al, 2005 (Fukae et al, 2010). Although pathology in Behçet's associated myelitis is not available, autopsy studies in neuro-Behçet's found intraparenchymal plasma cell and monocellular infiltrates as well as thrombosed medium-size veins consistent with a vasculitic process (Kocer et al, 1999).…”
Section: Behçet's Diseasementioning
confidence: 99%